2010
DOI: 10.1039/b921170e
|View full text |Cite
|
Sign up to set email alerts
|

The importance of chain connectivity in the formation of non-covalent interactions between polymers and single-walled carbon nanotubes and its impact on dispersion

Abstract: In this study we investigate the formation of non-covalent electron donor-acceptor (EDA) interactions between polymers and single-walled carbon nanotubes (SWNTs) with the goal of optimizing interfacial adhesion and homogeneity of nanocomposites without modifying the SWNT native surface. Nanocomposites of SWNTs and three sets of polymer matrices with varying composition of electron donating 2-(dimethylamino)ethyl methacrylate (DMAEMA) or electron accepting acrylonitrile (AN) and cyanostyrene (CNSt) were prepare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 61 publications
0
50
0
Order By: Relevance
“…The Journal of Physical Chemistry B ARTICLE These orientations are very different from that for a similar diameter carbon nanotube, which would have the same local curvature but, due to the availability of a 1D periodic axis along the nanotube, could support face-down orientations. 57 We also mention that, in general, the interaction energies between spatially small monomers and C 60 tend to be larger than those for single-walled carbon nanotubes when the orientation of the monomers are the same in part due to the presence of pentagons in the sp 2 network of C 60 .…”
Section: Resultsmentioning
confidence: 98%
“…The Journal of Physical Chemistry B ARTICLE These orientations are very different from that for a similar diameter carbon nanotube, which would have the same local curvature but, due to the availability of a 1D periodic axis along the nanotube, could support face-down orientations. 57 We also mention that, in general, the interaction energies between spatially small monomers and C 60 tend to be larger than those for single-walled carbon nanotubes when the orientation of the monomers are the same in part due to the presence of pentagons in the sp 2 network of C 60 .…”
Section: Resultsmentioning
confidence: 98%
“…41 Indeed, Beless et al demonstrated that substituted biphenyl compounds, such as those in E7, are able to adsorb efficiently onto carbon nanotubes provided the aromatic rings were not sterically hindered against entering a plane with each other. 42 The electron deficient cyano group, present on all the components of E7, are known to interact with SWCNTs 43,44 via the formation of a charge transfer complex. Harrison et al reported cyano-SWCNT charge-transfer complexes to be the cause on upshifts in the SWCNT G band of þ4 cm…”
mentioning
confidence: 99%
“…(c) The addition of the polymer to the solvent results in a considerable improvement of the MWCNT dispersion already at low sonication times as it is illustrated by the distinct decrease of the integral transmission of PCCL and PCcomp dispersions compared to CL dispersions. It can be assumed that polycarbonate chains wrap around the dispersed MWCNTs which is attributed to the high binding energy of the polymer containing aromatic phenyl rings resulting in a high interfacial adhesion with the MWCNTs as discussed by Linton et al [25] for polystyrene wrapping at SWCNTs. Covered by a polymer layer, the MWCNTs are not able to rebundle due to an entropic repulsion among the polymer-decorated MWCNTs which exceeds the van der Waals interactions of the nanotubes [27].…”
Section: Sedimentation Behaviour Of Mwcnts In Chloroform and Polymer mentioning
confidence: 98%
“…Some authors discussed polymer wrapping at CNTs, which was specifically used to improve the dispersion of CNTs in water [23] or organic solvents [24]. Theoretical studies reported the effective wrapping of polymers containing aromatic phenyl rings due to a high binding energy of the polymer resulting in high interfacial adhesion with SWCNTs [25] and postulated a dependency of the interaction strength of the CNT with the polymer on the number of repeating units in the polymer [26]. The group of Szleifer and Yerushalmi-Rozen suggested the decoration of SWCNTs with end-tethered polymers as the entropic repulsion among the tethered chains generates a free energy barrier that prevents the SWCNTs from approaching [27,28].…”
Section: Introductionmentioning
confidence: 99%